2015
DOI: 10.1371/journal.pone.0131216
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell-Mediated Phagocytosis but Not Immune Activation Is Enhanced by Plasmin

Abstract: Removal of dead cells in the absence of concomitant immune stimulation is essential for tissue homeostasis. We recently identified an injury-induced protein misfolding event that orchestrates the plasmin-dependent proteolytic degradation of necrotic cells. As impaired clearance of dead cells by the innate immune system predisposes to autoimmunity, we determined whether plasmin could influence endocytosis and immune cell stimulation by dendritic cells – a critical cell that links the innate and adaptive immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 46 publications
6
59
0
Order By: Relevance
“…It remains to be determined whether other NCC-resistant proteins are released from necrotic cells, but this seems highly likely (for reasons provided below with figures 4 and 5). The capacity of FUS and other NCC-resistant proteins to act as paracrine communicators of injury should now be assessed, especially given the influence of NCC on the proteolytic [10,20] and phagocytic [21] removal of dead cells. It will also be interesting to see if FUS released from necrotic cells has a role during FUS-mediated amyotrophic lateral sclerosis [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be determined whether other NCC-resistant proteins are released from necrotic cells, but this seems highly likely (for reasons provided below with figures 4 and 5). The capacity of FUS and other NCC-resistant proteins to act as paracrine communicators of injury should now be assessed, especially given the influence of NCC on the proteolytic [10,20] and phagocytic [21] removal of dead cells. It will also be interesting to see if FUS released from necrotic cells has a role during FUS-mediated amyotrophic lateral sclerosis [37].…”
Section: Resultsmentioning
confidence: 99%
“…NCC causes many intracellular proteins, including actin, tubulin, GAPDH and HSP90β, to convert from a soluble form into high-molecular-weight insoluble species [10]. In vitro and in vivo data show that NCC-aggregated proteins promote activation of the extracellular protease plasmin on the surface of dead cells [10,20,21]. Surface-bound plasmin then initiates two forms of clearance: direct proteolytic degradation of dead cells [10,20] and signalling nearby dendritic cells to increase their phagocytic capacity [21].…”
Section: Introductionmentioning
confidence: 99%
“…Plasmin has been described as a promoter of inflammation, yet recent findings suggest a more complex role in the modulation of immunity, including its ability to induce a tolerogenic phenotype to dendritic cells by reducing their capacity to induce an allogeneic immune response . Curiously, studies using plasminogen‐deficient mice have reported both reduced and exacerbated inflammatory responses, depending on the disease model: plasmin(ogen) deficiency can be deleterious in models of wound healing, yet protective in models of lipopolysaccharide‐induced and experimental autoimmune encephalomyelitis‐induced neuroinflammation indicating that plasminogen is needed to exert a complete inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…It has been implicated in inflammatory processes by direct interaction with proinflammatory and anti‐inflammatory mediators as well as various leukocyte subsets, by binding to cell‐surface plasminogen receptors and inducing intracellular signaling . In contrast, monocyte‐derived dendritic cells treated with plasmin exhibit enhanced phagocytic capacity, yet a reduced ability to migrate to the draining lymph nodes and to mount an allogeneic immune response …”
Section: Introductionmentioning
confidence: 99%
“…In addition, plasmin activity promotes phagocytosis by both macrophages 4 and dendritic cells. 5 This involves both recognition of prey and direct effects on engulfment of prey, events which are regulated by plasmin-mediated activation of intracellular signaling pathways that regulate expression of major genes involved in phagocytosis. 4 There may be an analogous mechanism for cellular fibrin uptake.…”
Section: Veterans Administration San Diego Healthcare Systemmentioning
confidence: 99%